Moderating Impact of Ownership Structure on Relationship of Equity Market Timing with Capital Structure on Companies Listed on Indonesia Stock Exchange - Irni Yunita; Rina Indiastuti; Ria Ratna Ariawati; Erie Febrian (Faculty of Business, President University, 2018)
The purpose of this research is to determine the effect of market to book ratio on leverage change with ownership structure as moderating variable. The research sample is 41 companies in Indonesia Stock Exchange which conducted IPO in 2005 - 2010. The analysis period is five years after an IPO. The independent variable is market to book ratio, the dependent variable is leverage change and control variable is tangibility, profit and size. The moderating variables are managerial and institutional ownerships which included as ownership structure. This research is using data panel regression. The results show that companies in Indonesia pursued the equity market timing strategy because there is a positive effect of market to book ratio into equity issue and negative effect of market to book ratio into leverage change. The results also show that institutional ownership structure moderating the equity market timing. However, managerial ownership does not moderating the equity market timing.